2002
DOI: 10.1063/1.1497454
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir probe diagnostic studies of pulsed hydrogen plasmas in planar microwave reactors

Abstract: Langmuir probe techniques have been used to study time and spatially resolved electron densities and electron temperatures in pulse-modulated hydrogen discharges in two different planar microwave reactors (f microwave = 2.45 GHz, t pulse = 1 ms). The reactors are (i) a standingwave radiative slotted waveguide reactor and (ii) a modified travelling-wave radiative slotted waveguide reactor, which generate relatively large plasmas over areas from about 350 cm 2 to 500 cm 2 . The plasma properties of these reactor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…To determine radial distributions for T e measurement corrections, we inserted equations (2)-(5) into the equation (6), which resulted in the following expressions: (7), (8) and (9), we obtained similar measurement correction dependencies for the remaining three plasma parameters, n e , V s , and j es as graphically shown in figures 5-7. According to these dependencies, errors in T e measurements reached about 7%, for n e -up to 14%, for V s -up to 20%, and for j es -up to 28 %.…”
Section: Correction Of Measurement Results Obtained By the Main Probe-1mentioning
confidence: 95%
See 2 more Smart Citations
“…To determine radial distributions for T e measurement corrections, we inserted equations (2)-(5) into the equation (6), which resulted in the following expressions: (7), (8) and (9), we obtained similar measurement correction dependencies for the remaining three plasma parameters, n e , V s , and j es as graphically shown in figures 5-7. According to these dependencies, errors in T e measurements reached about 7%, for n e -up to 14%, for V s -up to 20%, and for j es -up to 28 %.…”
Section: Correction Of Measurement Results Obtained By the Main Probe-1mentioning
confidence: 95%
“…Therefore, in this situation, plasma state could hardly feel the presence of a probe in plasma. That is why probe leads were usually surrounded by bare metal shields to protect them against RF interferences [5,6]. According to our previous works, where the behavior of large conducting bodies immersed in plasma was analyzed qualitatively, it was found that such bodies self consistently acquired single plasma floating potential at the point close to the minimal floating potential beside the body.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that ordinary probes containing metal tip inside dielectric capillary do not provide reliable results in microwave plasma since they were strongly perturbed by the electromagnetic field of the microwave. 19 Therefore, shielded probes, made from solid coaxial rod that was comprised of an external copper layer on a floating potential surrounding its inner 2-mm radius dielectric and a 1-mm radius metal core, were utilized. The metal tip of the probe that was exposed to the plasma was made from a nickel-chromium (Ni-Cr) alloy spot welded to the inner metal core of the solid coaxial rod.…”
Section: Plasma Reactor and Probe Systemmentioning
confidence: 99%
“…Plasma diagnostic, allowing to identify transient species, as well as stable products and other properties involved in plasma processing, has become a powerful method to understand the mechanisms which ultimately lead to the growth of films of the most diverse characteristics [19][20][21]. The diagnostic is mainly carried out with spectroscopic techniques like visible emission of excited species [6,[22][23][24][25] or infrared absorption of molecular bands [7,[26][27][28][29][30]; by mass spectrometry of neutrals [1][2][3]6,31,32] and ions [33][34][35], and with Langmuir probes [36,37].…”
Section: Introductionmentioning
confidence: 99%